Effects of summer and winter harvesting on element phytoextraction efficiency of Salix and Populus clones planted on contaminated soil. Issue 5 (16th April 2018) - Kubátová, Pavla; Száková, Jiřina; Břendová, Kateřina; Kroulíková-Vondráčková, Stanislava; Mercl, Filip; Tlustoš, Pavel
ABSTRACT: The clones of fast-growing trees (FGTs) were investigated for phytoextraction of soil contaminated with risk elements (REs), especially Cd, Pb, and Zn. As a main experimental factor, the potential effect of biomass harvesting time was assessed. The field experiment with two Salix clones (S1 – (Salix schwerinii × Salix viminalis) × S. viminalis, S2 – S. × smithiana) and two Populus clones (P1 – Populus maximowiczii × Populus nigra, P2 – P. nigra) was established in April 2009. Shoots of all clones were first harvested in February 2012. After two further growing seasons, the first half of the trees was harvested in September 2013 before leaf fall (summer harvest) and the second half in February 2014 (winter harvest). Remediation factors (RFs) for all clones and all REs (except Pb for clone S1) were higher in the summer harvest. The highest annual RFs for Cd and for Zn (1.34 and 0.67%, respectively) were found for clone S2 and were significantly higher than other clones. Although no increased mortality of trees harvested in the summer was detected in the following season, the effect of summer harvesting on the phytoextraction potential of FGTs clones should be investigated in long-term studies.